FAKTOR YANG BERKORELASI TERHADAP MEKANISME KOPING PASIEN CKD YANG MENJALANI HEMODIALISIS DI RSUD KOTA SEMARANG (Correlating factors of coping mechanism on CKD patients undergoing Hemodialysis in RSUD Kota Semarang) - Yunie Armiyati; Desi Ariyana Rahayu (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2014)
Chronic Kidney Disease (CKD) patients who undergo hemodialysis can experience a variety ofproblems that arise as a result of a malfunction of the kidneys and hemodialysis process. Thoseproblems will cause stres and different coping mechanism, such as maladaptive copingmechanism. Nurses need to identify the various factors that correlate to the patient's copingmechanism in order to help identify contributing factors. The purpose of this study is to analyzethe factors that contribute to coping mechanism of CKD patients undergoing hemodialysis. Thisresearch used descriptive correlation design with samples of 39 hemodialysis patients at RSUDKota Semarang. The results show that there is no correlation between age and coping mechanism of response (p = 0.976> 0.05), there is a correlation between length of CKD withcoping mechanism (p = 0.015 <0.05), there is a correlation between length of undergoing HDwith coping mechanism (p = 0.002 <0.05) and there is a significant correlation betweenreceived of stres response to coping mechanisms (p = 0.008 <0.05), the more positive responseof receiving stres, the more adaptive coping mechanisms that is used by the patients.Recommendation of this study is that nurses can apply effective stres management for patients,so that the patient's coping mechanism become more adaptive.Keywords: Coping mechanism, Chronic Kidney Disease (CKD), Hemodialysis